Allies or Enemies: The Role of Reactive Oxygen Species in Developmental Processes of Black Cottonwood (Populus trichocarpa) - Katarzyna Marzec-Schmidt; Natalia Wojciechowska; Klaudia Nemeczek; Agnieszka Ludwików; Joanna Mucha; Agnieszka Bagniewska-Zadworna (MDPI AG, 2020)
In contrast to aboveground organs (stems and leaves), developmental events and their regulation in underground organs, such as pioneer and fine roots, are quite poorly understood. The objective of the current study was to achieve a better understanding of the physiological and molecular role of reactive oxygen species (ROS) and ROS-related enzymes in the process of stem and pioneer root development in black cottonwood (Populus trichocarpa), as well as in the senescence of leaves and fine roots. Results of a transcriptomic analysis revealed that primary/secondary growth and senescence are accompanied by substantial changes in the expression of genes related to oxidative stress metabolism. We observed that some mechanisms common for above- and under-ground organs, e.g., the expression of superoxide dismutase (SOD) genes and SOD activity, declined during stems’ and pioneer roots’ development. Moreover, the localization of hydrogen peroxide (H2O2) and superoxide (O2•−) in the primary and secondary xylem of stems and pioneer roots confirms their involvement in xylem cell wall lignification and the induction of programmed cell death (PCD). H2O2 and O2•− in senescing fine roots were present in the same locations as demonstrated previously for ATG8 (AuTophaGy-related) proteins, implying their participation in cell degradation during senescence, while O2•− in older leaves was also localized similarly to ATG8 in chloroplasts, suggesting their role in chlorophagy. ROS and ROS-related enzymes play an integral role in the lignification of xylem cell walls in Populus trichocarpa, as well as the induction of PCD during xylogenesis and senescence.